Less Advanced Stages of Colon Cancer in Patients with Type 2 Diabetes Mellitus: an Unexpected Finding? - Nagel, J. M.; Bücker, S.; Wood, M.; Stark, R.; Göke, B.; Parhofer, K. G.; Allgayer, H. (Experimental and Clinical Endocrinology & Diabetes, 2012)
Epidemiological studies have found an increased risk for colon cancer and faster disease progression in patients with type 2 diabetes mellitus (T2DM). We aimed to determine whether patients with T2DM are diagnosed with more advanced stages of colorectal cancer, i. e., metastasized disease (UICC III and IV), at the time of diagnosis, since such a finding may have an impact on future guidelines for patients with T2DM.A cross-sectional analysis of colorectal cancer patients was performed. Stages at diagnosis in patients with (18.0%) or without (82%) T2DM were compared using logistic regression analysis to correct for confounders.Patients with T2DM were older, more obese, and more often male (each p<0.05). Unexpectedly, patients with T2DM had a lower risk for metastasized disease at diagnosis (p=0.023). Correction for age, gender, BMI, smoking and aspirin intake in a multiple logistic regression analysis did not change the result (OR=0.57, p=0.037). When looking at individual cancer stages rather than collapsed categories, there was a trend for less advanced stages in patients with T2DM (p=0.093). Excluding stage I because of potential screening bias due to the introduction of (insurance-covered) colonoscopy screening improved model fit, and confirmed less advanced cancer stages (p=0.0246).Possibly because of earlier detection, patients with T2DM may be at lower risk for advanced stages of colon cancer at diagnosis. Further studies are warranted to confirm our results and to investigate the impact of closer medical surveillance in patients with type 2 diabetes mellitus.
Keywords: type 2 diabetes mellitus; colon cancer; diagnosis; stage